2016
DOI: 10.21273/hortsci11172-16
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Onion (Allium cepa) Plant Growth and Bulb Yield and Quality as Affected by Potassium and Sulfur Fertilization Rates

Abstract: ‘Vidalia’ onions are sweet, short day, low pungency, yellow Granex-type bulbs that are popular in the United States. The relationships of sweet onion bulb yield and quality with potassium (K) and sulfur (S) concentrations are not fully understood. The objective of this study was to evaluate the effects of K and S fertilization rates on sweet onion plant growth and bulb yield and quality. Experiments were conducted at the Horticulture Farm, Tifton Campus, University of Georgia, in the Winters of 2012–13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
3
5
1
Order By: Relevance
“…Here, the high moisture percentage (>91%) confirm that Nerokremmydo should be treated as a fresh mild onion with reduced shelf life [70], implying a relatively short period of availability in local markets. According to our findings (Table 5), bulb %DM averaged 8.17%, which is similar to that of other sweet onions [72,73]. The development of plant % DM (Table 4) shows that its greatest increase occurred after bulbing and up to harvest, in agreement with relevant findings of other researchers [74,75].…”
Section: Discussionsupporting
confidence: 91%
“…Here, the high moisture percentage (>91%) confirm that Nerokremmydo should be treated as a fresh mild onion with reduced shelf life [70], implying a relatively short period of availability in local markets. According to our findings (Table 5), bulb %DM averaged 8.17%, which is similar to that of other sweet onions [72,73]. The development of plant % DM (Table 4) shows that its greatest increase occurred after bulbing and up to harvest, in agreement with relevant findings of other researchers [74,75].…”
Section: Discussionsupporting
confidence: 91%
“…In another report, the addition of nutrients via soil or foliar biofertilizer was unable to supply the required nutrients and was responsible for generating imbalances which decreased the growth and development of the onion crop (Menezes J unior et al, 2013). The mean mineral nutrient concentrations of onion bulbs under organic fertilization in the present study differed compared with the bulb nutrient concentrations under inorganic fertilization of the K and S study (Díaz-P erez et al, 2016). Bulb N (1.84% vs. 2.00%), S (0.22% vs. 0.48%), and Zn (14 vs. 61 mg · kg -1 ) concentrations were lower whereas concentrations of P (0.45% vs. 0.30%), K (2.14% vs. 1.24%), Ca (0.64% vs. 0.25%), Mg (0.24% vs. 0.10%), B (24 vs. 17 mg · kg -1 ), Fe (76 vs. 40 mg · kg -1 ), and Mn (163 vs. 141 mg · kg -1 ) were higher in this study compared with the K and S study, indicating that utilization of organic fertilization resulted in more mineral nutrient-rich bulbs.…”
Section: Discussioncontrasting
confidence: 75%
“…In a study on the effects of K and S inorganic fertilization rates on sweet onion conducted on the same farm as the present study, simultaneously, and using the same cultivar and cultural practices, mean root, bulb, and shoot dry weights of mature plants (at harvest time) were 1.3, 23.1, and 12.7 g/plant, respectively (Díaz-P erez et al, 2016). Results of the present study showed that compared with the onion plants of the K and S study, root growth was enhanced by up to 31% in plants under organic fertilization (at rates $180 kg · ha -1 N).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Potassium (K + ) is a macronutrient required for fundamental physiological and molecular processes in plants [ 20 ]. It is probably involved in the development of stronger cell walls for preventing the entry of plant pathogens into the cell [ 21 ].…”
Section: Introductionmentioning
confidence: 99%